2015
DOI: 10.1002/pc.23491
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interfacial adhesion in carbon fiber/poly (acrylonitrile‐butadiene‐styrene) composite through fiber surface treatment by an emulsion sizing

Abstract: To improve the interfacial adhesion between carbon fiber (CF) and poly (acrylonitrile-butadiene-styrene) (ABS) thermoplastic, an emulsion sizing whose film former was a terpolymer N-phenylmaleimide-styrenemaleic anhydride (NSM)/ABS mixture was prepared. NSM, an efficient heat-resistant modifier for ABS, could make the film former possess a superior heat resistance, which helped the sizing layer maintain integrity during the preparation of CF/ABS composite. Moreover, differential scanning calorimetry (DSC) resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Several papers have been reported on ABS composites re reinforced with carbon fiber and carbon nanoparticles earlier 21–26 . J. Li et al 22 reported that the fiber surface treatment with HNO 3 played a significant role in increasing the tensile strength and modulus carbon fiber/ABS composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have been reported on ABS composites re reinforced with carbon fiber and carbon nanoparticles earlier 21–26 . J. Li et al 22 reported that the fiber surface treatment with HNO 3 played a significant role in increasing the tensile strength and modulus carbon fiber/ABS composites.…”
Section: Introductionmentioning
confidence: 99%
“…Jyoti et al 26 highlighted that ABS composites with multi‐wall carbon nanotubes well‐dispersed using a micro twin‐screw extruder exhibited efficient electromagnetic interference shielding properties, due to significant improvement in the electrical conductivity and the improved mechanical properties. So far, no papers have been dealing with the effect of A, B, and S components on various properties of carbon fiber/ABS composites produced by LFT process although there have been several studies on carbon/ABS composites reported earlier 21–26 …”
Section: Introductionmentioning
confidence: 99%
“…They found that the ILSS of the sized CF‐reinforced composites reached 57.63 MPa; this was an increase of 29.16% compared with that of the composite with desized CFs. Ma et al . enhanced the interfacial adhesion between CFs and a poly(acrylonitrile–butadiene–styrene) thermoplastic with an emulsion sizing agent prepared with modified poly(acrylonitrile–butadiene–styrene).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that sizing agent improve the degree of wettability of the CF as well as the interface interaction between CF and polymer. [29][30][31][32][33] It is critical to synthesize a polymer with similar structures comparable to PPEK's. In addition, it must also possess a high temperature tolerance.…”
Section: Introductionmentioning
confidence: 99%